2018
DOI: 10.1002/jcb.26824
|View full text |Cite
|
Sign up to set email alerts
|

Reelin regulates male mouse reproductive capacity via the sertoli cells

Abstract: Reelin plays important roles in brain development. Reeler mutant mice that lack the protein reelin (RELN) suffer from cell type‐ and region‐dependent changes in their neocortical layers, and adult reeler mutant mice have dilated seminiferous tubules. Meanwhile, the mechanism by which Reelin regulates the spermatogenic cell development in mice and their reproductive abilities remains unclear. In the present study, we used reeler mutant mice to investigate the effects of Reelin on reproduction in mice. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Accumulating studies have indicated that various signaling pathways in SCs are implicated with spermatogenesis 27,28 . Until now, numerous signaling pathways have been found in Sertoli cells, including the androgensignaling pathway 29,30 , the AMP-activated protein kinase (AMPK) signaling pathway 31 , the follicle stimulating hormone (FSH)/adenylate cyclase/cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) signaling pathway 32 , the Hippo signaling pathway 33,34 , the intergrin mediated signaling pathway 4,35 , the Janus kinase/signal transducer and activator of transcription signaling pathway 36,37 , the mitogen-activated protein kinases (MAPK) signaling pathway [38][39][40][41][42][43][44] , the nuclear factor kappa B signaling pathway 45,46 , the nitric oxide/soluble guanylyl cyclase/cyclic guanosine monophosphate/ protein kinase G signaling pathway 47,48 , the Notch signaling pathway 49 , the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3k)/AKT serine/threonine kinase (Akt) signaling pathway 50,51 , the Sonic Hedgehog signaling pathway 52,53 , the transforming growth factor-β (TGF-β)/ Smad signaling pathway 54 , and the Wnt signaling pathway 55,56 (Table 1). Among all these signaling pathways, the TGF-β/Smad, AMPK, and MAPK signaling pathways have attracted much more attentions in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have indicated that various signaling pathways in SCs are implicated with spermatogenesis 27,28 . Until now, numerous signaling pathways have been found in Sertoli cells, including the androgensignaling pathway 29,30 , the AMP-activated protein kinase (AMPK) signaling pathway 31 , the follicle stimulating hormone (FSH)/adenylate cyclase/cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) signaling pathway 32 , the Hippo signaling pathway 33,34 , the intergrin mediated signaling pathway 4,35 , the Janus kinase/signal transducer and activator of transcription signaling pathway 36,37 , the mitogen-activated protein kinases (MAPK) signaling pathway [38][39][40][41][42][43][44] , the nuclear factor kappa B signaling pathway 45,46 , the nitric oxide/soluble guanylyl cyclase/cyclic guanosine monophosphate/ protein kinase G signaling pathway 47,48 , the Notch signaling pathway 49 , the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3k)/AKT serine/threonine kinase (Akt) signaling pathway 50,51 , the Sonic Hedgehog signaling pathway 52,53 , the transforming growth factor-β (TGF-β)/ Smad signaling pathway 54 , and the Wnt signaling pathway 55,56 (Table 1). Among all these signaling pathways, the TGF-β/Smad, AMPK, and MAPK signaling pathways have attracted much more attentions in the past decade.…”
Section: Introductionmentioning
confidence: 99%